UPAYA MENINGKATKAN HASIL BELAJAR IPAS MELALUI PROJECT BASED LEARNING BERBASIS BAHAN DAUR ULANG - Maghfirah Adelia; Suhelayanti; Yustizar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning outcomes of fifth-grade students of SD 3 Bayeun in science subjects through the implementation of the Project-Based Learning (PjBL) model with recycled materials. The background of this study is the low level of student engagement in learning which results in less than optimal learning outcomes. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model implemented in two cycles. The subjects of the study were 14 fifth-grade students of SD 3 Bayeun. Data collection techniques include observation, testing, and documentation. The project given was in the form of making a relief map using recycled materials in the form of used paper and cardboard. Data were analyzed qualitatively and quantitatively through the calculation of average scores and percentage of learning completion. The results of the study showed an increase in student learning outcomes in each cycle. The percentage of learning completion increased from 28.57% in the pre-test stage to 57.14% in cycle I and increased again to 92.86% in cycle II. Therefore, the implementation of the Project Based Learning model based on recycled materials was effective in improving students’ IPAS learning outcomes